If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8a + -12 = 12 Reorder the terms: -12 + 8a = 12 Solving -12 + 8a = 12 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 8a = 12 + 12 Combine like terms: -12 + 12 = 0 0 + 8a = 12 + 12 8a = 12 + 12 Combine like terms: 12 + 12 = 24 8a = 24 Divide each side by '8'. a = 3 Simplifying a = 3
| 7y=2+3 | | 12m+9+7-1=20 | | 2b-3=16 | | a^2+b^2+c^2=d^2 | | 4x+1-5=12 | | x^2=3x+5 | | 12y-5=2 | | 4a+4=8 | | 3x^2+17x-6= | | 3x^2+17-6= | | 2X+35-15=20 | | 49-64x^2=0 | | 5n+25g=5.65 | | -7x-3y-2+7x= | | x+5y=57 | | x+5y= 57 | | -3x+4y=76 | | -6b+13b= | | 12b+3+2=20 | | n=2(l+w)-4 | | 3-(Inj(1))=3a | | 9c+7=21 | | 5x^6-125X^4=0 | | 7y=4y+8 | | 3-In(1)=3a | | -(-4)= | | 12a-7=15 | | 4y=7y+8 | | 8i+4=10 | | -5x-3x+x= | | 14x-2(x-9)+21= | | 3(2x-2)-2(3x+4)= |